Does small and medium enterprise differential leadership increase subordinate knowledge hiding? Evidences from job insecurity, territorial consciousness and leadership performance expectation - Xu, Jing; Zhu, Dequn; Li, Yongzhou (Frontiers in Psychology, 2022)
Leadership is considered as a significant antecedent of knowledge hiding in SMEs (small and medium enterprises), but the differential dimension of leadership has been evidently neglected in both theoretical and empirical areas. Drawing on conservation of resource theory and social cognitive theory, this research investigates whether and how SME differential leadership influences subordinate knowledge hiding. Specifically, we analyze the underlying mechanisms of a chain--mediator—job insecurity and territorial consciousness and a boundary condition—leadership performance expectation. Multi-wave and multi-source data were collected from a sample of 704 Chinese SME employees and 140 relevant leaders and applied HLM meso-mediational frameworks, and Bootstrap technique with nonparametric percentile residuals for deviation correction. The results show that differential leadership plays a potential role in promoting subordinate knowledge hiding through the serial intervening mechanism of job Insecurity and territorial consciousness in SMEs. Furthermore, the positive relationship between SME differential leadership and job insecurity becomes stronger among subordinates under higher leadership performance expectation; the positive indirect relationship between SME differential leadership and subordinate knowledge hiding is stronger with higher levels of leadership performance expectation. This study contributes to the existing academic literature by empirically analyzing the under-investigated correlation between differential leadership and subordinate knowledge hiding in SMEs, and by exploring the underlying mechanisms and a boundary condition.